Analisis Perencanaan Pembelajaran (ATP, Modul Ajar, dan Lesson Plan) - Deswita Siagian; Rahmad Mulia Abdi Lubis; Mariam Nasution (Yayasan Darussalam Bengkulu, 2026)
Learning planning is an important aspect of improving the quality of education because it serves as a guideline for implementing a directed, systematic, and effective teaching and learning process. In the implementation of the Merdeka Curriculum, learning tools such as the Learning Objectives Flow (ATP), teaching modules, and lesson plans become the main components that help teachers design learning activities in accordance with learning outcomes and students’ needs. ATP functions to organize learning objectives systematically and continuously, teaching modules help make learning more structured, flexible, and contextual, while lesson plans assist teachers in carrying out classroom learning activities effectively and efficiently. This study aims to analyze the roles, functions, advantages, and implementation of ATP, teaching modules, and lesson plans based on reviews of national and international journals. The research method used is a literature review by collecting, examining, and analyzing various scientific journals related to learning planning in the Merdeka Curriculum. The results of the study indicate that ATP, teaching modules, and lesson plans have interconnected roles in creating a more directed, structured, and student-centered learning process. However, their implementation still faces several challenges, such as teachers’ limited understanding, lack of training, schools’ inadequate readiness, and limited supporting facilities and infrastructure. Therefore, continuous training, mentoring, and teacher competency development are needed so that the implementation of learning planning tools in the Merdeka Curriculum can run optimally and contribute to improving the quality of education